Reflective playwork for all who work with children - Kilvington, Jacky; Wood, Ali (New York Bloomsbury Academic, 2018)
This text provides an introduction to playwork values, principles and practice for all who work with children. It recognizes that play is a need for all, and seeks to encourage the provision of time and space for all children to freely enjoy its benefits.
1. The playwork approach -- 2. Play -- 3. A new paradigm for play -- 4. The child -- 5. playwork practice -- 6. Children's play and welfare -- 7. Playable spaces -- 8. Continuing professional development.
"First edition published 2009"--Title page verso.
Includes bibliographical references and index.
Keywords: Play (Philosophy).; Child development; Creative ability in children